Tradisi Pembacaan Surah Yāsin di MIS Miftahul Falaah Kediri (Studi Living Hadis) - Prafita, Evi Dwi Intan Mey; Latifah, Eny Nurul; Robingatun, Robingatun (Canonia Religia, 2024)
This article aims to reveal the meaning of the recitation of surah Yāsin conducted at MIS Miftahul Falaah, Kediri. This tradition has been running since 2017. It is carried out every Friday morning, starting at 07.00 WIB and finishing. There are two focuses of study in this research, namely how the meaning of the practice of reciting surah Yāsin at MIS Miftahul Falaah, Kediri, and how the transmission of hadith helped construct the practice. This research includes field research and is studied using qualitative research methods. Data were collected through interviews, observations, and documentation studies. Furthermore, data analysis was carried out using descriptive qualitative, in which researchers tried to describe the tradition of reciting surah Yāsin at MIS Miftahul Falaah, Kediri along with the meaning and normative basis for the practice. Based on the results of the research, there are several things related to the motivation of the school in carrying out the practice of reciting surah Yāsin, including: first, to worship and get closer to Allah Swt; second, to pray for the deceased with the belief that reading surah Yāsin can free themselves from hellfire; third, to pray for students, especially grade V so as not to repeat past events (conflicts with teachers), and to pray for grade VI students to be given ease and smoothness in carrying out school exams. Several of these motivations are also closely related to the virtues of surah Yasin mentioned in the hadith narration: as qalbu al-Qur'an (the heart of the Qur'an) because of its virtues and facilitates the affairs of those who read it. Although many consider it dla'if, these reports do not affect the firm belief in reviving this chapter of the Qur'an in the community, especially at MIS Miftahul Falaah.